Beneficial effect of antidepressants against rotenone induced Parkinsonism like symptoms in rats. Issue 2 (June 2016) - Sharma, Nidhika; Jamwal, Sumit; Kumar, Puneet
Abstract: Parkinson's disease is a second most common age-related neurodegenerative disorder characterized by the loss of DA neurons of SNpc region of the midbrain. Neurotransmitter dysfunction is involved in the pathogenesis of PD. Antidepressants like venlafaxine and sertraline expected to improve Parkinsonism like symptoms by modulating the levels of various neurotransmitters. The neuroprotective role of antidepressants is well explored in various CNS disorders. Therefore, this study was designed to explore and compare the mechanistic role of different antidepressants (venlafaxine and sertraline) against rotenone induced Parkinsonism like symptoms in rats. Rats were administrated with rotenone (1.5 mg/kg/day; s.c.) daily for a period of 28 days. Venlafaxine (10 and 20 mg/kg; p.o.), sertraline (10 and 20 mg/kg; p.o.) and Levodopa combination with Carbidopa (10 mg/kg; p.o.) were administered daily starting from 7th day one hour prior to rotenone administration. Behavioral parameters (body weight, rotarod, grip strength, narrow beam walk and open field) were assessed on weekly basis. On 28th day, animals were sacrificed and striatum were isolated for biochemical (LPO, GSH and nitrite), neuroinflammatory (TNF-α, IL-1β and IL-6), neurochemical (DA, NE, 5-HT, GABA, Glutamate, DOPAC, HVA and 5-HIAA) and mitochondrial complex-I estimation. Rotenone administration significantly reduced body weight, motor coordination, oxidative defense, increased pro-inflammatory mediators and decreased level of catecholamines. Pre-treatment with venlafaxine and sertraline significantly attenuated the alteration in behavioral, oxidative stress, neuroinflammatory, mitochondrial and catecholamines level in striatum. The study provides a hope that these drugs could be used as adjuvant therapy in the management and treatment of PD.